Effective practices for improving service professionals’ ethical behaviors: A multiple method study - Hu, Ying; Yang, Yefei; Lee, Peter K. C. (Frontiers in Psychology, 2022)
Enhancing frontline professional service employees’ ethics has been an increasingly important issue for organizations in sustaining their reputation and long-term profitability. While many organizations have implemented general ethics programmes such as ethics codes and ethical training, unethical scandals regularly still appear in many service organizations. This research offers new insights into the practices that can effectively enhance marketing practitioners’ ethical behaviours and the pertinent contextual factors that have a bearing on the effectiveness of ethics programmes. It uses a multi-method methodology to conduct two studies in the Chinese banking setting. Based on the rank of revenue and profitability published by Fortune magazine of year 2021, in Study 1, we choose five main Chinese banking organizations to conduct case studies to explore the framework of effective ethics programmes of banks. In Study 2 we use the valid instruments from the literature to measure the involved constructs and employs data from randomly selected 146 frontline banking teams in five main Chinese banking organizations to examine the effectiveness of three specific ethics practices and ascertain the moderating role of role stress in such effectiveness. Our findings indicate the effective behaviour control practices within organizations’ ethics programmes and the implications of having a stressful workplace when adopting such practices. In addition, our findings integrate organizational concepts regarding behaviour control and employee ethics, and uses two empirical methods to systematically explore the effectiveness of ethics programmes. Moreover, our findings advance the management and marketing literature and have significant managerial implications for improving frontline service professionals’ ethical behaviours.